Опыт применения метода таксономического анализа в зоогеографических исследованиях (на примере жужелиц) - Михалевич, О.А.; Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1978)
Entomogeographic division of the Crimea is tested using the method of taxonomic analysis of E. S. Smirnov. The similarity and difference between some regions are found. Four groups of the regions are distinguished: plain, mountain, intermediate and south-coastal. The Jajla area is the most peculiar among the Crimean regions. Biogeographic nomenclature of the considered territory is regulated.